2019
DOI: 10.1017/s0305741019000845
|View full text |Cite
|
Sign up to set email alerts
|

Examining Public Concern about Global Warming and Climate Change in China

Abstract: AbstractTo what degree are Chinese citizens concerned about the seriousness of global warming and climate change (GWCC) and what are the key factors that shape their concern? Drawing theoretical insights from extant literature and using recent data from a national representative public survey (N = 3,748) and provincial environmental and economic statistics, this study, the first of its kind, examines the variations and determinants of Chinese GWCC concern. Our data show that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 69 publications
0
12
1
Order By: Relevance
“…Eco-feminism has emerged as an ethics pointing to linked structural oppression of women and other marginalized groups, including animals and plants (e.g., Warren 1994;Gaard 2001). Also in China, we observe a tendency for women to be more concerned about climate change and environmental destruction than men (Liu et al 2020;Liu and Mu 2016;Lou 2017;Lee and Han 2015). A 2019 research report from the Ministry of Ecology and Environment highlighted a survey which even suggested that women also performed better than men when protecting their immediate environment.…”
Section: Introductionmentioning
confidence: 78%
“…Eco-feminism has emerged as an ethics pointing to linked structural oppression of women and other marginalized groups, including animals and plants (e.g., Warren 1994;Gaard 2001). Also in China, we observe a tendency for women to be more concerned about climate change and environmental destruction than men (Liu et al 2020;Liu and Mu 2016;Lou 2017;Lee and Han 2015). A 2019 research report from the Ministry of Ecology and Environment highlighted a survey which even suggested that women also performed better than men when protecting their immediate environment.…”
Section: Introductionmentioning
confidence: 78%
“…The polarity of the views with regard to the urgency is demystified by a study in China [28]. The authors reported that on the global scale the average public concern about the GWCC among Chinese citizens are relatively low, further analysis revealed that youth and women with greater post-materialist values had more concern about GWCC than that of their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the control and modified samples was compared. The water absorption results are expressed as a percentage of dry weight of the specimens Equation (2).…”
Section: Determination Of Water Absorption Testmentioning
confidence: 99%
“…Global warming impasse like extreme heat waves, sea level rise, acid rain, flooding, warmer ocean temperatures, and melting of Antarctica occurs more than ever in recent decades because of rise in fossil fuel and nonrenewable energy consumption. [1][2][3] Land degradation owing to forest burning and landfill for waste disposal reduces productivity of dryland on the ecosystems and unfortunately, waste generation is steadily increasing and becoming a source of great concern. Clinical waste from hospitals and other health facilities is on the rise because of increasing population, unhealthy lifestyle and now the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%